ANALISIS KUALITAS PELAYANAN BRT TRANS SEMARANG KORIDOR II RUTE TERBOYO – SISEMUT - Fika Rachmawati; Ida Hayu Dwimawanti; Rihandoyo Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The quality of services is one of a measure to judge public services. Bus Rapid transit (BRT) is one basic needs of the community of semarang in the field of public transportation. However, service BRT Trans Semarang Corridor II is not in accordance with the desire of the community. Now many damaged bus shelter and some shelters are not strategic. The purpose ofthis research is to analyze and describe service BRT Trans Semarang Corridor II by using ten indicators the quality of services is city transportation security, the accuracy of, regularity, comfort, the speed, pleasure, satisfaction, affordability, transparency, and the strategy and service system.Researchers used statistical data analysis techniques to analyze data with an average descriptive mean that the results are classified into four that is very good, good, bad, and very bad. There are six sub indicators are classified as bad among others is cleanliness in shelters , the bus stops, facilities in shelters, lighting in shelters, ease reporting missing goods, affordability of the shelters, discriminatory and services. To the highest average price affordability is on the sub indicators 3,19 worth.While for the lowest average that is lighting in shelters with value is 2,09.The results of this research as a whole that is the quality of transportation services BRT Trans Semarang Corridor II had been good but not optimal because there are several sub indicators bad. Need of an improvement on the shelters and affordability of the shelter .